Reliability and validity of the CogState battery Chinese language version in schizophrenia. - Na Zhong (Public Library of Science (PLoS), 2013)
Background Cognitive impairment in patients with schizophrenia is a core symptom of this disease. The computerized CogState Battery (CSB) has been used to detect seven of the most common cognitive domains in schizophrenia. The aim of this study was to examine the reliability and validity of the Chinese version of the CSB (CSB-C), in Chinese patients with schizophrenia. Methodology/principal findings Sixty Chinese patients with schizophrenia and 58 age, sex, and education matched healthy controls were enrolled. All subjects completed the CSB-C and the Repeated Battery for the Assessment of Neuropsychological Status (RBANS). To examine the test-retest reliability of CSB-C, we tested 33 healthy controls twice, at a one month interval. The Cronbach α value of CSB-C in patients was 0.81. The test-retest correlation coefficients of the Two Back Task, Gronton Maze Learning Task, Social Emotional Cognition Task, and Continuous Paired Association Learning Task were between 0.39 and 0.62 (p<0.01) in healthy controls. The composite scores and all subscores for the CSB-C in patients were significantly (p<0.01) lower than those of healthy controls. Furthermore, composite scores for patients on the RBANS were also significantly lower than those of healthy controls. Interestingly, there was a positive correlation (r = 0.544, p<0.001) between the composite scores on CSB-C and RBANS for patients. Additionally, in the attention and memory cognitive domains, corresponding subsets from the two batteries correlated significantly (p<0.05). Moreover, factor analysis showed a two-factor model, consisting of speed, memory and reasoning. Conclusions/significance The CSB-C shows good reliability and validity in measuring the broad cognitive domains of schizophrenia in affected Chinese patients. Therefore, the CSB-C can be used as a cognitive battery, to assess the therapeutic effects of potential cognitive-enhancing agents in this cohort.